INNOVATIVE APPROACHES TO TEACHING METHODS: BRIDGING TRADITIONAL PRACTICES WITH MODERN PEDAGOGY IN 21ST CENTURY CLASSROOMS - Xasanova Zarrina Shadiyarovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Teaching methods have evolved considerably over the centuries, transitioning from teacher-centered to more student-focused approaches. Traditional pedagogies, such as lectures and textbook-based instruction, continue to play a crucial role in education but are increasingly being complemented by modern, innovative practices like active learning, collaborative techniques, and the use of technology. This article examines the evolution of teaching methods, highlights innovative strategies, and provides a framework for blending traditional and modern pedagogies. By synthesizing these approaches, the article offers insights into how educators can better meet the diverse learning needs of students in the 21st century.